La pedagogía del amor en el desarrollo afectivo en la Educación Inicial del grupo 2 de la Unidad Educativa Vicente León en el año lectivo 2020 - 2021. - Cela Toaquiza, María Cristina (2021)
This research reveals the relationship between the pedagogy of love and the emotional development in children of Initial Education at "Vicente León" Educational Unit, to form integral humans able to feel, doing and being by themselves. It is a proposal that allows the teacher to accompany to the student in a total way with the aim of strengthening the affective area through the application of this pedagogy, providing theoretical support based on the development and exercising of affectivity, which makes it possible for children to express freely, where they can play and have fun. This research work has a quantitative and qualitative approach which allowed to collect data and analyze variables. Besides, it let Early Childhood Education children were able to strengthen emotional bounds among family members through traditional games, they also improved their self-esteem through the acquisition of habits which stimulated their freedom, confidence and security, it helps them to develop emotional intelligence helping to reach integration with the educational community; it was possible to complement the traditional pedagogy with the pedagogy of love through methodological strategies of affection and tenderness, being an educational model that stimulates the teacher to put in practice their authentic vocation, based on understanding and tolerance along with their values and virtues, concluding that affectivity is important in children’s lives, especially in the educational field, therefore, it is necessary to “Educate with our heart”.